Clinical and epidemiological evaluation of influenza and SARS-CoV-2 coinfected cases - Yeliz Çiçek; Hıdır Sarı; Duygu İmre Yetkin; Mehmet Özel (Journal of Infection in Developing Countries)
Introduction: Coinfection of COVID-19 with influenza pathogens, may complicate the diagnosis, treatment, and prognosis, which is a new concern. This study aims to evaluate COVID-19 and influenza coinfected cases during the flu season, while the SARS-CoV-2 pandemic continues.